Recent advances in Clostridium difficile-associated disease. Issue 1001 (7th April 2009) - Monaghan, T; Boswell, T; Mahida, Y R
Abstract : The main purpose of this article is to review recent developments in the management of acute and recurrent Clostridium difficile -associated disease, with consideration of existing and new antibiotic and non-antibiotic agents for treatment. Details of the current developmental stage of new agents are provided and the role of surgery in the management of severe disease is discussed. Infection control measures considered comprise prudent use of antimicrobials, prevention of cross-infection and surveillance. Other topics that are covered include the recent emergence of an epidemic hypervirulent strain, pathogenesis, clinical presentation and approaches to rapid diagnosis and assessment of the colonic disease.